2011
DOI: 10.1017/s1473550411000012
|View full text |Cite
|
Sign up to set email alerts
|

A wide variety of putative extremophiles and large beta-diversity at the Mars Desert Research Station (Utah)

Abstract: Humankind's innate curiosity makes us wonder whether life is or was present on other planetary bodies such as Mars. The EuroGeoMars 2009 campaign was organized at the Mars Desert Research Station (MDRS) to perform multidisciplinary astrobiology research. MDRS in southeast Utah is situated in a cold arid desert with mineralogy and erosion processes comparable to those on Mars. Insight into the microbial community composition of this terrestrial Mars analogue provides essential information for the search for lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 64 publications
(96 reference statements)
3
74
0
1
Order By: Relevance
“…The core microbiome of this study has a different composition than those reads found only in individual samples, with the aforementioned preponderance of Thermoprotei. This is perhaps not unexpected, as Crenarchaeota contains radio-and thermotolerant species detected previously in other extreme environments, including desert soils (16,21), hot springs (75), permafrost (80), and marine environments near the Sonoran Desert (8). The rare OTUs appear to be relatively similar in terms of the proportion of various phyla between sample sites.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The core microbiome of this study has a different composition than those reads found only in individual samples, with the aforementioned preponderance of Thermoprotei. This is perhaps not unexpected, as Crenarchaeota contains radio-and thermotolerant species detected previously in other extreme environments, including desert soils (16,21), hot springs (75), permafrost (80), and marine environments near the Sonoran Desert (8). The rare OTUs appear to be relatively similar in terms of the proportion of various phyla between sample sites.…”
Section: Discussionsupporting
confidence: 72%
“…PCR amplification of the 16S rRNA gene and subsequent pyrosequencing were carried out at the Australian Centre for Ecogenomics (http://www.ecogenomic.org/) as previously described (21). Briefly, broad-specificity oligonucleotide primers 926F (F stands for forward) (5=-AAACTYAAAKGAATTGACGG-3=) and 1392R (R stands for reverse) (5=-ACGGGCGGTGTGTRC-3=) containing multiplex identifiers and LibL adaptor sequences (see Table S1 in the supplemental material) were used to generate amplicons spanning the hypervariable regions of the 16S rRNA gene from V6 to V9 (22).…”
Section: Methodsmentioning
confidence: 99%
“…MDRS, in Utah, is an arid, oxidizing environment with high temperatures during the day and low temperatures at night. MDRS has a mineralogy comparable to that found on Mars and a patchy distribution of biomarkers and microorganisms (Clarke and Stoker, 2011;Direito et al, 2011;Ehrenfreund et al, 2011;Martins et al, 2011). Parts of Mars may have been highly acidic and saline in the past, resembling conditions currently found at Río Tinto, Spain.…”
Section: Conclusion and Perspectivementioning
confidence: 76%
“…); the Mars desert research station (UT; Direito et al. ); sunlight‐exposed biofilms from Chernobyl (Ukraine; Ragon et al. ); and saline biological desert crusts (China; Li et al.…”
Section: Resultsmentioning
confidence: 99%